Targeted Plasma Bile Acid Metabolomic Analysis in Metabolic Dysfunction-Associated Steatohepatitis and Alcoholic Hepatitis - Yuta Hirata; Yasunaru Sakuma; Hideo Ogiso; Ryozo Nagai; Kenichi Aizawa (Biomedicines)
Background: Even though many metabolic liver diseases can now be diagnosed using blood tests and diagnostic imaging, early diagnosis remains difficult. Understanding mechanisms contributing to the progression from Metabolic Dysfunction-Associated Steatohepatitis (MASH) and Alcoholic Hepatitis (AH) to cirrhosis is critical to reduce the burden of end-stage liver disease. Monitoring individual bile acids has been proposed as a way to distinguish various liver disorders. Methods: This study explored bile acid profiles in patients with MASH and AH. Plasma samples from patients with MASH, AH, and a control group were analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) to quantify bile acid concentrations. Targeted metabolomic analysis was performed to compare bile acid levels between the hepatitis and control groups. Results: Concentrations of ursodeoxycholic acid (UDCA), chenodeoxycholic acid (CDCA), taurocholic acid (TCA), tauroursodeoxycholic acid (TUDCA), taurochenodeoxycholic acid (TCDCA), glycoursodeoxycholic acid (GUDCA), glycochenodeoxycholic acid (GCDCA), and glycocholic acid (GCA) were significantly elevated in the hepatitis group. Correlation analysis revealed strong positive relationships between the total and direct bilirubin levels and TUDCA and GCDCA. Aspartate aminotransferase (AST) showed strong positive correlations with TCDCA and GCDCA. Child–Pugh score, Fibrosis-4 index, and non-alcoholic fatty liver disease fibrosis score were positively correlated with GCA, whereas the aspartate aminotransferase-to-platelet ratio correlated with TCA, TCDCA, and GCA. The model for end-stage liver disease (MELD) score showed a strong positive correlation with GCDCA. Implications: GCDCA may serve as a predictive biomarker for liver damage, potentially enabling early diagnosis and targeted intervention in patients with MASH and AH.